THE INFLUENCE OF INDUSTRIAL INTERNSHIP AND SELF-EFFICACY ON STUDENT WORK READINESS OF HVACR ENGINEERING COMPETENCY - Pratama, Rizqie Akbar; Putra, Ragil Randi Ratmaja (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2024)
Vocational High School (SMK) graduates are graduates who have the highest Open Unemployment Rate (TPT) among other levels of education. Low work readiness is one of the contributing factors. The purpose of this study was to analyze the influence of industrial internship and self-efficacy on students work readiness. The method used in this study was ex-post facto with a quantitative approach. The data collection technique used a questionnaire with a value range between 1 to 5 likert scale models. Respondents in this study were grade XII students of Heating, Ventilation, Air Conditioning and Refrigeration (HVACR) Engineering Competency at SMKN 8 Bandung. This study consisted of three variables, namely industrial internship (X1), self-efficacy (X2) and students work readiness (Y). The data analysis technique used was multiple regression analysis. The results showed that internship and self-efficacy had a positive and significant effect on students work readiness. Therefore, students work readiness can be through the improvement of industrial internship program and self-efficacy.